Association between quality of life, confinement, and sex in adults: a multigroup structural equation analysis - Zurita Ortega, Félix.; Galeano Rojas, Dilan.; Tenelanda López, Dennys.; Cresp Barría, Mauricio.; Farías Valenzuela, Claudio Ítalo.; Valdivia Moral, Pedro. (MDPI, 2024)
The state of confinement during the COVID-19 pandemic affected the quality of life of the general population. This study aims to define and contrast an explanatory model of the quality of life in adults and to analyze the relationships between these variables based on the state of confinement and sex. A total of 872 people from Chile aged between 17 and 50 (M = 21.70 years; SD= 3.272), of both sexes (60.90% male and 39.1% female) participated in this research, of whom 46.6% were not confined when tested and 53.4% were confined, analyzing the quality of life. A model of multi-group structural equations was performed, which adjusted very well (χ2 = 559.577; DF = 38; p < 0.001; IFC = 0.934; NFI = 0.916; IFI = 0.934; RMSEA = 0.061). The results show a positive and direct relationship among all the variables studied and the structural equation model proposed according to confinement and sex reveals a good fit in all the evaluation indexes. Stress and sleep, personality, and introspection were the indicators with the greatest influence in the four models, followed by the family and friends indicator with a medium correlation strength, such as the health monitoring dimension, although this was not as influential in confined individuals. The main conclusions are that the best adjustments are obtained in confined adults and females, and the data show that the psychological indicators obtained (stress and sleep, personality, and introspection) have the greatest influence on adults in the four models proposed with regard to their quality of life.
Keywords: Confinement; Estilos de vida; Calidad de vida; Sexo